0=2(6+5n)+-1(8n+8)

Simple and best practice solution for 0=2(6+5n)+-1(8n+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=2(6+5n)+-1(8n+8) equation:


Simplifying
0 = 2(6 + 5n) + -1(8n + 8)
0 = (6 * 2 + 5n * 2) + -1(8n + 8)
0 = (12 + 10n) + -1(8n + 8)

Reorder the terms:
0 = 12 + 10n + -1(8 + 8n)
0 = 12 + 10n + (8 * -1 + 8n * -1)
0 = 12 + 10n + (-8 + -8n)

Reorder the terms:
0 = 12 + -8 + 10n + -8n

Combine like terms: 12 + -8 = 4
0 = 4 + 10n + -8n

Combine like terms: 10n + -8n = 2n
0 = 4 + 2n

Solving
0 = 4 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
0 + -2n = 4 + 2n + -2n
Remove the zero:
-2n = 4 + 2n + -2n

Combine like terms: 2n + -2n = 0
-2n = 4 + 0
-2n = 4

Divide each side by '-2'.
n = -2

Simplifying
n = -2

See similar equations:

| 3x+5(-9-3x)=15 | | 16+x=8 | | X=80-45 | | -6-7r-14=32+6r | | 9x^3+8x^2+225x+200=0 | | 92x=220 | | 0=2(6+5n)-(8n+8) | | 25d+100=250 | | 33+7=25 | | 25d+125=250 | | 5+8=6 | | -16z-18=4z | | 8(x-3)-8=-96 | | 123=3x-6(-2x+7) | | .25x-.30(x-5)=5x | | -4(x+5)+2y=-22 | | 12x+14=2x+84 | | 14x+16=8x+28 | | -32=w-3 | | 13x+42=6x+91 | | 50+.8m=150 | | -12+4(3-x)=-32-28 | | x+4x+(5x+15)=180 | | 2(x+4)2=19 | | -3(6-x)+6=6-5(x+2) | | 12x^2+28x+16= | | x+(-x+5)=-2 | | 16=(1.8c)+32 | | 11,067x-5208=93(119x-56) | | .75*e-16=2-.125*e | | 75+.8m=150 | | .75e-16=2-.125e |

Equations solver categories